FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN MANUFAKTUR DI INDONESIA TAHUN 2018-2020 - Limanjaya, Vinson; Santioso, Linda (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this research is to find out empirically the effect of profitability, liquidity, capital structure, firm size, and dividend policy on firm value. The population used in this study are manufacturing companies listed on the Indonesian Stock Exchange (IDX) from 2018 to 2020. The sample selection method used is purposive sampling. The companies used as research objects are 42 companies out of a total of 168 companies listed on IDX. Data processing techniques using multiple regression analysis what helped by Eviews 12 Program for Windows and Microsoft Excel 2019. The results obtained from this study are that profitability has a positive and significant effect on firm value, liquidity and firm size have positive and insignificant effect on firm value, capital structure has a negative and significant effect on firm value and dividend policy has a negative and insignificant effect on firm value. The implication of this study is to increase the role of management to create good decision that will increase the firm value.